Pengaruh Penerapan Iso 9001 dan Kualitas Produk Pada Keputusan Pembelian - Amelia Sholeha; Mayang Sari; Bunga Cintia; Alifah Sajidah; Firda Alfi Ningtyas (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
This study examines the effect of ISO 9001 implementation and product quality on Purchasing Decisions. This study uses a quantitative method with primary data through a survey to collect data. Respondents in this study were employees of PT Epson Indonesia, with the number of employees who were sampled was 30 employees. The sampling method used in the study was purposive sampling, while the data processing method used the Corrected Item to Total Correlation method for validity testing and the Cronbach's Alpha method for reliability testing. The results showed that from 15 question instruments related to the ISO 9001 variable, product quality, and Purchasing Decisions were declared valid with a significant percentage of 0.05 or 5% and were declared consistent/reliable with Cronbach's alpha of 0.938> 0.60.